KELIMPAHAN PENYAKIT KARANG DI KEPULAUAN AYAU DAN ASIA KABUPATEN RAJA AMPAT - Ofri Johan; Purwanto Purwanto; Irman Rumengan; Awaludinnoer Awaludinnoer (Pusat Riset Perikanan, Badan Riset dan Sumber Daya Manusia Kelautan dan Perikanan, 2020)
Kematian karang dapat disebabkan oleh beberapa faktor, salah satunya diakibatkan oleh adanya infeksi penyakit karang. Terbatasnya data dan informasi keberadaan penyakit karang saat ini menyebabkan kelimpahan penyakit karang belum banyak diketahui di Indonesia. Penelitian bertujuan untuk mendapatkan jenis dan kelimpahan penyakit karang, serta penilaian kondisi terumbu karang yang dilakukan pada delapan lokasi di kawasan the coral triangle. Hasil penelitian diperoleh tiga jenis penyakit karang dengan kelimpahan berturut-turut adalah black band disease (0,03 kol/m2), white syndrome (0,03 kol/m2), dan bleaching (0,05 kol/m2). Sementara penyakit skeleton eroding band ditemukan di luar lokasi pengamatan. Kondisi terumbu karang pada lokasi pengamatan termasuk dalam kategori sangat jelek hingga kondisi sedang. Kelompok penganggu kesehatan karang berhasil didata sebanyak delapan kriteria penganggu di antaranya pigmentation response, kompetisi ruang antara alga, spons dan karang lunak, predasi akibat hewan Drupella sp., Acanthaster plancii, dan bekas pemangsaan ikan. Kelimpahan penyakit ini tergolong rendah, namun perlu pengamatan secara kontinu untuk mengetahui dampak infeksi penyakit karang terhadap kerusakan terumbu karang di masa akan datang.Coral die-offs can be caused by several factors, one of which is the infectious coral disease. Currently, limited data and information are available regarding coral diseases in Indonesia. Such condition has resulted in the relatively poor understanding of the extent and distribution of coral diseases in Indonesia’s reef ecosystem. The purpose of this research was to investigate types and abundance of coral disease as well as determine the overall health condition of infected coral reef. The research was carried out in eight sites in the waters around Ayau Islands and Asia Island, which belong to the Raja Ampat Marine Protected Area (MPA). This study found that the areas’ coral health condition varied from bad to poor. The study also successfully identified three coral diseases in the sites with varying degrees of infection and distribution. The identified coral diseases were black band disease, white syndrome, and bleaching, each with a maximum abundance of 0.03 col/m2, 0.03 col/m2, and 0.05 col/m2, respectively. The study also identified skeleton eroding band disease, which infected the coral reef system outside of the surveyed sites. Assessment on the health condition of coral had found eight compromising factors, which included pigmentation response, spatial competition among algae, sponges and soft corals, as well as predation by Drupella sp., Acanthaster plancii, dan reef fishes. This study concludes that the level of coral disease abundance in the area can be classified as low. However, a regular survey has to be carried out in the area to monitor the progress and distribution of the coral diseases and measure their future impacts on the coral reef ecosystem of the MPA.